2022
DOI: 10.3341/kjo.2022.0017
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Two Swept-Source Optical Coherence Tomography Biometers and a Partial Coherence Interferometer

Abstract: Purpose: To evaluate the level of agreement between ANTERION (Heidelberg Engineering, Heidelberg, Germany), OA-2000 (Tomey, Nagoya, Japan), and IOLMaster 500 (Carl Zeiss AG, Jena, Germany).Methods: Fifty-one eyes of 51 patients were included in the study. Flat keratometry (K) and steep K, vector component of astigmatism (Jackson cross-cylinder at 0° and 90° [J<sub>0</sub>] and Jackson cross-cylinder at 45° and 135° [J<sub>45</sub>]), anterior chamber depth, and axial length were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…The mean difference between biometers was 0.12 mm, with limits of agreement of 0.03 and 0.21 mm. This difference was statistically significant as well as clinically relevant, considering the trend an overestimation of ACD with the VEMoS-AXL system and that the limits of agreement were in the range of those reported in studies comparing biometers and concluding that ACD measures were not interchangeable [ 5 , 6 , 13 , 14 , 15 , 16 , 17 ]. Moon et al [ 16 ] concluded that ACD measures obtained with Anterion and IOL-Master 500 systems were not interchangeable (limits of agreement, −0.33 to 0.22 mm) as well as ACD measurements obtained with OA-2000 and IOL-Master 500 biometers (limits of agreement, −0.37 to 0.20 mm).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The mean difference between biometers was 0.12 mm, with limits of agreement of 0.03 and 0.21 mm. This difference was statistically significant as well as clinically relevant, considering the trend an overestimation of ACD with the VEMoS-AXL system and that the limits of agreement were in the range of those reported in studies comparing biometers and concluding that ACD measures were not interchangeable [ 5 , 6 , 13 , 14 , 15 , 16 , 17 ]. Moon et al [ 16 ] concluded that ACD measures obtained with Anterion and IOL-Master 500 systems were not interchangeable (limits of agreement, −0.33 to 0.22 mm) as well as ACD measurements obtained with OA-2000 and IOL-Master 500 biometers (limits of agreement, −0.37 to 0.20 mm).…”
Section: Discussionmentioning
confidence: 53%
“…This difference was statistically significant as well as clinically relevant, considering the trend an overestimation of ACD with the VEMoS-AXL system and that the limits of agreement were in the range of those reported in studies comparing biometers and concluding that ACD measures were not interchangeable [ 5 , 6 , 13 , 14 , 15 , 16 , 17 ]. Moon et al [ 16 ] concluded that ACD measures obtained with Anterion and IOL-Master 500 systems were not interchangeable (limits of agreement, −0.33 to 0.22 mm) as well as ACD measurements obtained with OA-2000 and IOL-Master 500 biometers (limits of agreement, −0.37 to 0.20 mm). Cheng et al [ 17 ] compared different biometers, confirming the presence of a poor agreement of ACD measures obtained with some of them: Anterion vs. OA-2000 (−0.19 to 0.28 mm), OA-2000 vs. IOL-Master (−0.19 to 0.25 mm), Anterion vs. Lenstar (−0.04 to 0.21 mm), and OA-2000 vs. Lenstar (−0.16 to 0.23 mm).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations